Kinetic Study of Calcium Phosphate Precipitation in the System H3PO4-Ca(OH)2-H2O at 30°C - K. Labgairi; A. Borji; M. Kaddami; A. Jourani (International Journal of Chemical Engineering)
The precipitation kinetics of calcium phosphates, namely, hydroxyapatite (HAP), dicalcium phosphate dihydrate (DCPD), dicalcium phosphate anhydrous (DCPA), and monocalcium phosphate monohydrate (MCPM), were studied at 30°C by mixing calcium hydroxide, water, and phosphoric acid. The studied mixture was selected according to the stability domain of different calcium phosphates by referring to the phase diagram of the ternary system of H3PO4-Ca(OH)2-H2O at 30°C. The precipitation reaction has been monitored by following the changes in the conductivity, pH, and calcium concentration. The solid phases formed at different stages of this precipitation were characterized by X-ray diffraction.